TOOLS FOR COURSE PREPARATION IN METRIC COMPETENCE FORMAT (Revista Inclusiones, 2019)
Currently, the determination of the quality of training is the most important task. In our work, we use the definition of quality monitoring according to ABC-abilities, which are defined by N.K.Nuriyev and L.N. Zhurbenko. According to them, competence in any field is invariantly supported by the triad of abilities of a certain level of development, i.e. ABC abilities and knowledge, as auxiliary means, where A, B, C are formalization, constructive and performing abilities, respectively. The course editor in the form of a written application is developed in the form of a web-based student training program that allows to evaluate and visualize the level of ABC - a student's abilities. Based on these results, a decision is made on the trajectory of further education.